BurnBLITZ: your pocket-sized personal trainer / Noor Azila Azreen Md Radzi ... [et al.]. - Md Radzi, Noor Azila Azreen; Mohamed, Muhamad Noor; Raja Hussain, Raja Nurul Jannat; Saari, Maisarah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
“Unlock the power of exercise right at your fingertips, making fitness more accessible than ever.” As a sports science enthusiast and a tech-savvy person, we have always been fascinated by the intersection of technology and physical fitness. This passion led us to develop BurnBLITZ, an innovative app designed to empower individuals to achieve their fitness goals. Built with the user-friendly Adalo platform, BurnBLITZ offers a comprehensive exercise library, detailed instructions, and engaging visuals to guide users through their workouts. BurnBLITZ: More Than Just an App BurnBLITZ is not merely an app; it is a virtual fitness companion that caters to people of all fitness levels. At its core, it is a knowledge repository brimming with exercise information, presented in a visually appealing and easy-to-follow format. Whether you are a seasoned athlete looking to enhance your performance or a beginner taking your first steps toward a healthier lifestyle, BurnBLITZ has something to offer.